The Role Of Agricultural Extenders In Participation In The Implementation Of No-Till Cultivation Systems (TOT) On Corn Plant In Simpang Village, Bantarkalong District: - Azis, Irsyad Abdul; Umbara, Dona Setia; Heryadi, D. Yadi (CV. Utami, 2025)
Corn is an agricultural commodity being developed in Simpang Village, Bantarkalong District, Tasikmalaya Regency. However, the participation of the Waluya III Farmers Group in corn cultivation is still below standard, mainly due to obstacles in obtaining fertilizer as needed. This study aims to analyze the influence of agricultural extension workers on farmer participation in the implementation of the No-Tillage System (TOT). The method used is a survey with a quantitative descriptive approach through observation and distribution of questionnaires to farmer group members. Data analysis was carried out using SPSS through partial tests (t-test) and simultaneous tests (F-test) at a significance level of 0.05. The results showed that all roles of extension workers, including facilitator, innovator, motivator, dynamicator, educator, and communicator, have a positive and significant effect on farmer participation. The significance value of the t-test and F-test of 0.000 <0.05 proves that the role of extension workers plays an important role in increasing farmer participation in the implementation of the TOT system.